We are not parasites: intergroup differentiation in the user-generated content of Nigerian news media (2019)
Studies have shown that despite the freedom of content creation and democratic participation, the digital space has also provided platforms for negative discourse with far-reaching implications for national unity and democracy. However, scant scholarly attention has been given to the prevalence and nature of online negative discourse in a pluralistic and politically complex society like Nigeria. Therefore, anchored on the Social Identity Theory (SIT), this study examined forms of intergroup discrimination as a negative discourse in the user-generated content (UGC) of online platforms of select Nigerian news media. Textual analysis of the UGC shows that as users react to news stories about national issues, they also create contents that reflect group identities and intergroup prejudices characterising Nigeria as a country with fragile unity. This phenomenon is a new socio-cultural order that poses serious threats to the peaceful co-existence and future of Nigeria—a nation grappling with sundry political, ethno-religious and security challenges.